Unusual Presentation of Kala Azar: A Case Series from Rajshahi Medical College Hospital, Bangladesh (Medicine Today, 2025)
Kala Azar, or visceral leishmaniasis, often manifests with a typical triad of fever of long duration, wt loss, and splenomegaly. Unusual manifestations can sometimes make the diagnosis and management difficult. This case series was conducted in the Department of Hematology, Rajshahi Medical College Hospital, Rajshahi, Bangladesh. This case presented unusual occurrences of a typical disease, Kala Azar, which were encountered. The clinical challenges of diagnosis and management highlight different therapeutic interventions and responses. All 4 cases of Kala Azar, with unusual presentations, were retrospectively analyzed. Clinical examination, history, laboratory investigations, results, diagnosis, and treatment responses were retrieved, and in-depth analyses were conducted. Present 4 cases of unusual diseases. One patient had a fever and cough, and pancytopenia was not described as a common manifestation of Kala Azar. His initial blood tests described non-reactive malarial slides, whereas the final bone marrow report described pancytopenia due to Kala Azar. The patient improved with amphotericin-B courses. The presentation of Kala Azar was unusual in some cases, which is why its clinical evaluation must be kept in mind in endemic areas. Conducting a profound evaluation and early management is essential.Medicine Today 2025, Vol.37 (2): 279-284